2004
DOI: 10.1007/s00192-004-1191-3
|View full text |Cite
|
Sign up to set email alerts
|

mRNA assessment for procollagen production in women with genuine stress urinary incontinence

Abstract: The aim of the study was to examine changes in the levels of mRNA for procollagen type I and III in women with or without genuine stress incontinence (GSI). The study was performed in the 2nd Department of Obstetrics and Gynecology of University of Athens. Sixty-eight women participated in the study and they were divided in two groups. We did not find statistically significant difference between the two groups of patients in relation to the amount of mRNA of procollagen type I and III (p>0.05), but the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Several of these investigators [17,19] also showed a similar finding within skin cells, suggesting that the observation within the pelvic tissues was not only a consequence of SUI, but probably represented an underlying systemic process of low collagen state. Although some have suggested that an alteration in the collagen type I to type III ratio may alter the pelvic connective tissues, both ex vivo [17] and in vivo [20] data from populations with SUI fail to support this view. Weakened pelvic floor support may result from lower collagen content, but also from alterations within the distribution of collagen fibres.…”
Section: Extracellular Matrix In Pfdmentioning
confidence: 98%
“…Several of these investigators [17,19] also showed a similar finding within skin cells, suggesting that the observation within the pelvic tissues was not only a consequence of SUI, but probably represented an underlying systemic process of low collagen state. Although some have suggested that an alteration in the collagen type I to type III ratio may alter the pelvic connective tissues, both ex vivo [17] and in vivo [20] data from populations with SUI fail to support this view. Weakened pelvic floor support may result from lower collagen content, but also from alterations within the distribution of collagen fibres.…”
Section: Extracellular Matrix In Pfdmentioning
confidence: 98%
“…Measurements of the N‐terminal propeptides of collagen type I (PINP) and III (PIIINP) in blood are also used as markers of collagen formation. Although a reduction in the amount of collagen in stress incontinence has been reported previously by several researchers (3), (11), (12), no significant changes in the levels of mRNA for procollagen types I and III have been observed (8). Collagen cross‐links have also been examined in incontinent subjects, and have been found either diminished (13), or unaltered with respect to the controls (3).…”
Section: Introductionmentioning
confidence: 76%
“…On the other hand, collagenolytic activity has been found unaltered despite the reduction of total collagen in the pubocervical fascia (3). Although tissue collagen content was low in some cases, no alteration in the amount of mRNA for collagen types I and III was observed between the continent and incontinent group (8). It was suggested that the difference in the quantity of protein could be a consequence of altered collagen metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations